Semiotic Analysis of Racism Using IP Man 4: The Finale - Muhammad` Afra Masyhur; Suprayogi Suprayogi (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Racism, prejudice and discrimination are complex things that occur in this world, according to Baldwin (2017) this is a broad social phenomenon and a field for research, complicated by the fact that intolerance exists in internal cognition but manifests in the use of symbols (verbal, nonverbal). , mediation), law and policy, and social and organizational practice. It is based on group identification (ie, understanding and treating a person or persons in terms of outgroup membership); but those outgroups can range from better-known outgroups based on race, gender/gender, nationality, or sexual orientation to more specific intolerance of others based on political party, fan status, or membership in some groups perceived as "blonde". " or "athlete." This article begins with the relationship of culture to prejudice, paying attention to certain culture-based prejudices about ethnocentrism and xenophobia. It then explores the degree to which prejudice might manifest, finally arriving at the specific focus of prejudice—racism; however, what applies to racism may also apply to other intolerances such as sexism, heterosexism, classicism, or ageism. This article considers that the issue of racism can occur because of the motivation that causes this to use Charles Peirce's semiotic theory.